A new method for measuring tail exponents of firm size distributions - Shouji Fujimoto; Atushi Ishikawa; Takayuki Mizuno; Tsutomu Watanabe (Economics: The Open-Access, Open-Assessment E-Journal, 2011)
The authors propose a new method for estimating the power-law exponents of firm size variables. Their focus is on how to empirically identify a range in which a firm size variable follows a power-law distribution. On the one hand, as is well known a firm size variable follows a power-law distribution only beyond some threshold. On the other hand, in almost all empirical exercises, the right end part of a distribution deviates from a power-law due to finite size effects. The authors modify the method proposed by Malevergne et al. (2011). In this way they can identify both the lower and the upper thresholds and then estimate the power-law exponent using observations only in the range defined by the two thresholds. They apply this new method to various firm size variables, including annual sales, the number of workers, and tangible fixed assets for firms in more than thirty countries.
Keywords: C16; C18; D20; E23; 330; econophysics; power-law distributions; power-law exponents; firm size variables; finite size effect; Betriebsgrößenstruktur; Statistische Verteilung; Econophysics; Theorie; Welt